PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI FINANSIAL, DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PT. COCA - COLA EUROPACIFIC PARTNERS INDONESIA – BALINUSA OPERATIONS - I Komang Yudi Pranata; I Gusti Agung Eka Teja Kusuma; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The company's biggest contribution to achieving optimal company performance and operations can be seen in employee performance. The theory used in this research is the Balance Theory. The purpose of this research is to determine the influence of leadership style, financial compensation, and organizational climate on employee performance. The research population was all employees of PT. Coca-Cola Europacific Partners Indonesia-Balinusa Operations, totaling 80 people, with the research sample using the entire population of 80 people using the Census Method. The data analysis technique used is Multiple Linear Regression Analysis, F Test and t Test. The research results show that the variables of leadership style, financial compensation, and organizational climate each have a positive and significant influence on employee performance. It is hoped that the results of this research can be used by PT. Coca-Cola Europacific Partners Indonesia-Balinusa Operations as consideration for making policies within the company so that it can improve the performance of future employees.